ANALISIS PERAN GURU MENERAPKAN KARAKTER TANGGUNG JAWAB PADA MASA PANDEMI COVID-19 DI SMP NEGERI 11 DUMAI - Desi Henzevrina Sianturi; Supentri Supentri; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Absrtact: This research is motivated by obstacles in the process of implementing education, especially during the COVID-19 pandemic, the implementation of face-to-face education cannot be carried out properly, so to apply the character of responsibility during the ongoing COVID-19 pandemic, the teacher must really work hard. in carrying out its role as a source of learning, as a demonstrator, as a guide, as a motivator, and as an evaluator. The formulation of the problem in this study is how is the role of the teacher in implementing the character of responsibility during the covid-19 pandemic at SMP Negeri 11 Dumai?. The purpose of the study was to find out how the role of teachers in implementing the character of responsibility during the covid-19 pandemic at SMP Negeri 11 Dumai. The benefits of this research can be a source of learning for all parties, especially for teachers, so that teachers can always carry out their role as teachers in the current situation. The research method is using quantitative descriptive, data collection instruments carried out in this study are questionnaires, interviews, observations, and documentation. The population in this study were all teachers at SMP Negeri 11 Dumai, totaling 23 people. The sample in this study was taken by all teachers at SMP Negeri 11 Dumai, totaling 23 people. Based on the results of the study, it can be concluded that the analysis of the role of teachers in applying the character of responsibility during the Covid-19 pandemic at SMP Negeri 11 Dumai is in the "Very Good" category. It can be shown from the results of the average percentage of the dominant respondents' answers, which is 91.7% which is in the "Very Good" category with a range of 75.01%-100%.Key Words : Teacher's Role, Responsibility Character, Covid-19 Pandemic Period.